"I know what you are going through": Answers to informational questions about eating disorders in Yahoo! answers: A qualitative study. Issue 1 (2013) - Bowler, Leanne; Mattern, Eleanor; Jeng, Wei; Oh, Jung Sun; He, Daqing
Abstract: The purpose of this study is to enrich our understanding of social question and answer (Q&A) sites as a health information source for teens. To do so we investigated answers to 81 informational questions about eating disorders posted in Yahoo! Answers, a social Q&A site. Through a content analysis, we found that users do not always respond to eating disorder questions with credible, factual information, even if the need for it was expressed in the question. The findings suggest that people who pose questions in Yahoo! Answers use it as a social and emotional scaffold rather than an informational source, even if their questions are couched in terms that suggest they are seeking information. Further, a large portion of the people who answer such questions understand this to be the purpose and rarely provide answers drawn from evidence‐based medicine or reliable, credible sources for health information. Through the investigation of the answers to questions on a health topic that is prevalent amongst teens, this study deepens our understanding of the health information behavior of young people and the quality of the health information they find in Yahoo! Answers .